Development of Listening and Speaking Skills Teaching Materials Based on CEFR Level - Primadana, Ramadhan Jabal; Maswani, Maswani; Wahab, Muhbib Abdul; Fudhaili, Achmad; Raswan, Raswan (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This research aims to develop effective and structured teaching materials in CEFR Level A1-A2-based Arabic listening and speaking skills for use in Alexandria Islamic School Bekasi. Unlike previous research that used CEFR for curriculum creation, this research focuses on the development of CEFR-based teaching materials. The CEFR standard is important in learning Arabic to assess the level of language proficiency. The research method used is Research and Development (R&D) with qualitative and quantitative approaches, and uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model developed by Dick and Carey. Data collection techniques include tests, observations, interviews, questionnaires, and documentation. The results of the study showed that the use of the textbook "Al-Arabiyyatu Kulla Yaumin" obtained an effectiveness level of 85%-100%, which was categorized as "excellent". This product has been tested at the Islamic School of Alexandria through pre-test and post-test, with validation results showing high effectiveness. The result of this study is a CEFR-based teaching material for Arabic listening and speaking skills at Level A1-A2 that is ready to use. This teaching material is expected to improve Arabic language learning systematically and effectively, as well as contribute to the development of Arabic language learning in Indonesia.